Improve the photovoltaic panels by advance cooling using distilled water and copper nanoparticles - Sultan Khalid F.; Fadel Hiba S.; Jaddoa A.A. (Karaganda National Research University named after academician E.A. Buketov, 2026)
This study aimed to cool photovoltaic panels (monocrystalline and polycrystalline) using advanced cooling techniques with pure water and copper nanoparticles. The problem addressed by the current study is the high temperature in solar panels, and this problem is addressed by using one of the advanced cooling methods using nanomaterials. The high temperature harms the performance of photovoltaic panels, so cooling them is important until the high temperature leads to a decrease in their efficiency. Nanoparticles have been identified as one of the most effective methods in cooling photovoltaic panels because of their properties that can help improve the efficiency of photovoltaic panels. This study aimed to cool photovoltaic panels (monocrystalline and polycrystalline), and K – type thermometers were used to measure the side temperature. The back of each panel every half hour and the use of a Multi meter digital to measure current and voltage per half hour and a solar radiation meter to measure the intensity of solar radiation. In general, monocrystalline panels achieved better than polycrystalline panels and the best improvement of output power was when using Nano fluid at a concentration of 5%. The output power of monocrystalline and polycrystalline panels (76, 81, 85, 89W) (65.48, 70, 74.5, 76W) respectively when using distilled water and Nano fluid at a concentration of (1, 3, 5 %).
Keywords: Photovoltaic; Thermal; Cooling; Nanoparticles; Concentration; Monocrystalline and Polycrystalline